A fuzzy group decision making model for multiple criteria based on Borda count - Anisseh, Mohammad; Mohd Yusuff, Rosnah (Academic Journals, 2011)
Most important decisions in organizations are made by groups of managers or experts. Methods for aggregating preferences and reconciling differences are needed in case decision makers have different viewpoints. Human judgments, including preferences are often vague and cannot be estimated in exact numerical values. This paper proposes a new method under the linguistic framework for heterogeneous group decision making. To accomplish this, an integrated fuzzy group decision making method based on Borda count is proposed, which allocates different weights for decision maker group members to use linguistic terms in order to express their fuzzy preferences for alternative solutions and for individual judgments. The proposed method is then supplied with a numerical example to illustrate the procedure and compare the results with other extant methods.